PENGARUH PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sukanti, Anisah Tri Woro; Rahmawati, Mia Ika (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This research aims to analyze and find out the effect of profitability, liquidity, and firm size on firm value. The profitability was measured by Return on Asset (ROA), liquidity was measured by Loan on Deposit Ratio (LDR), firm size was measured by Logarithm Natural (Ln) total asset, and firm value was measured by Price to Book Value (PBV). The research was quantitative. Moreover, the population was banking companies that were listed on Indonesia Stock Exchange (IDX) for 3 years (2019- 2021). The data collection technique used purposive sampling, which was used to gain an appropriate sample. In line with that, there were 87 companies as the sample. Furthermore, the data analysis technique, in order to examine the hypothesis, used multiple linear regression with SPSS. The research result concluded that profitability (ROA) had a positive effect on firm value. On the other hand, liquidity (LDR) had a negative effect on firm value. In contrast, firm size (SIZE) had a positive effect on firm value.